Biological Evaluation of 99mTc-Kanamycin for Infection Imaging - Eva Maria Widyasari; Iim Halimah; Rizky Juwita Sugiharti; Maula Eka Sriyani; Isti Daruwati; Iswahyudi Iswahyudi; Epy Isabela; Witri Nuraeni (Fakultas Sains dan Matematika Universitas Kristen Satya Wacana, 2017)
Kanamycin antibiotic was radiolabeled successfully with radioisotope technetium-99m for the potential use as radiopharmaceuticals for infection imaging. 99mTc-kanamycin complexes was prepared 93 % radiochemical purities by direct labelling using 5 mg kanamycin and 30 µg SnCl2. The reaction occurred at alkaline condition (pH=9) and under room temperature for 30 min to achieve high radiochemical purity. Radiochemical purity and stability of 99mTc-kanamycin was determined by ascending paper chromatography using Whatman 3 paper as the stationary phase, and acetone as the mobile phase to separate the radiochemical impurities in the form of 99mTc-pertechnetate. While impurities in the form of 99mTc-reduced were separated using the stationary phase ITLC-SG and 0.5 N NaOH as mobile phase. This study aimed to determine biological characteristic of 99mTc-kanamycin radiopharmaceutical. In vitro cell studies showed that the change of kanamycin structure after labeling with technetium-99m did not give a specific influence to the potency of kanamycin as an antibiotic. In addition on uptake study, a significantly higher uptake of 99mTc-kanamycin with S. aureus than E. coli. Biodistribution of 99mTc-kanamycin complexes was studied on normal and infection mice at 15, 30, 60 and 120 min post-injections. The biodistribution of 99mTc-kanamycin in infection mice showed that the complex accumulated in the infection sites. These results show that 99mTc-Kanamycin radiopharmaceutical have a potential application for infection diagnosis.